UMP, TM Seal MoU to Launch Metro-E, Wi-Fi - UMP, PNC
Universiti Malaysia Pahang (UMP) and Telekom Malaysia Bhd..(TM) recently marked another historical milestone when the two sealed a memorandum of understanding (MoU), with the latter agreeing to provide Metro-Ethernet (Metro-E) and wireless broadband (Wi-Fi) access services, connecting the two UMP campuses in Gambang and Pekan.